ANALISIS POTENSI EKOWISATA CURUG KEMBAR CISANGKU DI DESA WISATA MALASARI KABUPATEN BOGOR - Karmanah, Karmanah; Rusli, Abdul Rahman; Meiganati, Kustin Bintani; Gustira Putra, Mulyana (Jurnal Nusa Sylva, 2025)
The existence of the Cisangku Twin Waterfall managed by the Cisangku Conservation Village Model Group (MKK) has the potential to be developed into a nature-based ecotourism destination. The location of the waterfall is within the Mount Halimun Salak National Park area, supported by the presence of unique flora and fauna, making it a unique attraction as an environmentally friendly tourism destination. The development of the twin waterfall ecotourism needs to be organized and supported by complete facilities, services, accessibility, human resources, and waterfall management. The study aims to analyze visitor perceptions of tourism facilities and infrastructure and analyze the ecotourism potential of the Cisangku Twin Waterfall. The results show potential Based on visitor perceptions, more than 95% of visitors considered the location very clean, the air fresh and the service very good and the Curug Kembar ecotourism from the aspects of attraction, accessibility, facilities, and service received good ratings from visitors. The uniqueness of natural resources, natural beauty, and comfort of the Curug Kembar ecotourism also became an attraction with a value above 70%. Overall, the Curug Kembar ecotourism has great potential to continue to be developed as a nature conservation-based tourist destination in the Bogor Regency area.